2003
DOI: 10.1073/pnas.0237371100
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Pax4 in embryonic stem cells promotes differentiation of nestin-positive progenitor and insulin-producing cells

Abstract: Mouse embryonic stem (ES) cells differentiate into cells of all three primary germ layers including endodermal cells that produce insulin in vitro.We show that constitutive expression of Pax4 (Pax4 ؉ ), and to a lesser extent Pdx1 (Pdx1 ؉ ), affects the differentiation of ES cells and significantly promote the development of insulin-producing cells. In Pax4 overexpressing R1 ES cells, isl-1, ngn3, insulin, islet amyloid polypeptide, and glucose transporter 2 (Glut-2) mRNA levels increase significantly. The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
323
3
13

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 408 publications
(350 citation statements)
references
References 38 publications
11
323
3
13
Order By: Relevance
“…It has been shown that pancreatic cell types can be generated from mouse and non-human primate ESCs [10][11][12][13][14][15][16][17][18]. Based on these findings, recent studies have also suggested the potential of hESCs to differentiate into insulin-producing cells through spontaneous in vitro differentiation [5] or the use of a multi-stage protocol [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that pancreatic cell types can be generated from mouse and non-human primate ESCs [10][11][12][13][14][15][16][17][18]. Based on these findings, recent studies have also suggested the potential of hESCs to differentiate into insulin-producing cells through spontaneous in vitro differentiation [5] or the use of a multi-stage protocol [6].…”
Section: Introductionmentioning
confidence: 99%
“…Functional pancreatic cells, however, were successfully generated using lineage selection strategies based on pancreas-specific promoters [5,6], by modified protocols in combination with transgene expression [7][8][9], or by addition of a phosphoinositol-3 kinase inhibitor [10]. The differentiated cells showed properties of (neonatal) beta cells, such as insulin transcripts and C-peptide/insulin co-expression, insulin-secretory granules, ion channel activity of embryonal beta cells, and normalisation of blood glucose level after transplantation into diabetic mice [5][6][7][8][9][10]. Most of the differentiation protocols required a long cultivation period, including 4-5 days of embryoid body (EB) formation, followed by 3-4 weeks of differentiation, and some protocols required genetic manipulation.…”
mentioning
confidence: 99%
“…Instead, using the same differentiation protocol, it was found that insulin immunoreactivity occurred as a consequence of insulin uptake from the medium [2], neuronal cells were formed [2][3][4], or insulin was released as an artefact from differentiated ES cells [2,3]. Functional pancreatic cells, however, were successfully generated using lineage selection strategies based on pancreas-specific promoters [5,6], by modified protocols in combination with transgene expression [7][8][9], or by addition of a phosphoinositol-3 kinase inhibitor [10]. The differentiated cells showed properties of (neonatal) beta cells, such as insulin transcripts and C-peptide/insulin co-expression, insulin-secretory granules, ion channel activity of embryonal beta cells, and normalisation of blood glucose level after transplantation into diabetic mice [5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…The potential of IPCs generated from ESCs using embryoid body approach to normalize glucose in streptozotocin-induced diabetes mice is very low. Several reports indicated transient correction of blood glucose level after IPCs transplantation (Blyszczuk et al 2003;Hori et al 2002;Lumelsky et al 2001). This may be due to cell dying or dedifferentiation of transplanted IPCs.…”
Section: Differentiation Of Embryonic Stem Cellsmentioning
confidence: 99%
“…This may be due to cell dying or dedifferentiation of transplanted IPCs. Another problem regarding the ESCs differentiation into IPCs using embryoid body strategy is teratoma formation (Blyszczuk et al 2003;Hori et al 2002;Boyd et al 2008). A possible explanation for such a finding may be that IPCs are in fact a heterogenous mixture of undifferentiated ESCs, IPCs and even differentiated cells of other lineages.…”
Section: Differentiation Of Embryonic Stem Cellsmentioning
confidence: 99%